PENGGUNAAN PENDEKATAN KETERAMPILAN PROSES UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS IV SD - Mefrida, Mefrida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research is background 0f reality in praimery school SDN 15 ulu gadut pauh padang city, that old studing IPA is focust to the teacher so studing of studing of student is low. This research is research  in the classroom. This research is  con sit of nearly countitife and coalitife. This research is cow city of two kinds. The reality of the research to the planning, actitiy, and the finaly study of student to grow up, in the siclus one planning who pleaning by the teacher 64,2 get up tobe 82,1 at siclus two. Activity of teacher grate 70,8 to get up until 91,7 at siclus two. Activity student  grate 68,7 to get up until 87,5 at iclus two. The finaly student of student at siclus one oube 64,1 to get up 78,0 at siclus two. So nearly skillprocess getup reality IPA in pourth in SDN 15 Ulu Gadut Pauh Padang City. Kata kunci:    pendekatan keterampilan proses; hasil belajar;  IPA sd